The cuspal deflection caused by dental composite polymerization shrinkage analyzed by digital holography - Novta, Evgenije; Lainović, Tijana; Grujić, Dušan; Pantelić, Dejan; Blažić, Larisa (Vojnosanitetski pregled, 2023)
Background/Aim. Polymerization shrinkage of filling materials is one of the main disadvantages of adhesive restorative dentistry. The objective of the study was to measure tooth cusps deflection caused by polymerization shrinkage of a resin-based dental material (RDM) in real-time using digital holographic interferometry (DHI) in two groups of cavities restored with and without an additional wall. Simultaneously, internal tooth mechanical behavior was monitored. Methods. Standardized three class I cavities were prepared on third molar teeth. The teeth were cut in two halves in the longitudinal plane, obtaining six samples for the study (now with class II cavities), divided into two groups (group G1 – with the additional wall, group G2 – without it), and mounted in aluminum blocks. The cavities were filled with the RDM, cured with a light emitting diode (LED) for 40 sec from the occlusal direction, and monitored during the curing and post-curing period using DHI. Data were analyzed using the Student’s t-test for independent samples and the Anderson-Darling test, with an alpha level of 0.05. Results. At the end of the examined period, the samples from the group G1 showed significantly increased tooth cusps deflection [t (10) = 4.7; p = 0.001] compared to samples from the group G2. Conclusion. Within the limitations of this study, it was concluded that the presence of the additional wall simulating a dental matrix band had a significant influence on the increase and prolonged deflection of tooth cusps during the examined RDM polymerization shrinkage.